1980
DOI: 10.1172/jci109971
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vasopressin and prostaglandins in the toad urinary bladder.

Abstract: Arachidonic acid, the specific precursor of prostaglandin synthesis, increased PCE2 synthesis twofold, and significantly inhibited AVP-and DDAVP-stimulated water flow by 60 and 75%, respectively. Naproxen and acetaminophen inhibited prostaglandin synthesis and enhanced water flow in response to AVP and DDAVP (44-54%).Our findings indicate that the toad bladder produces two prostaglandins, PGE2 and TXB2, and that vasopressin does not alter their rate of synthesis. Because agents such as acetaminophen and naprox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1

Year Published

1981
1981
1992
1992

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
3
12
1
Order By: Relevance
“…Direct determination of PGE2 synthesis by intact bladders showed no effect of 10 AM trifluoperazine under either basal or vasopressin-stimulated conditions. Furthermore, vasopressin failed to increase PGE2 synthesis, consistent with out previous report (19). Trifluoperazine's inhibitory effect persisted in the presence of the prostaglandin synthesis inhibitor naproxen, offering further evidence against a prostaglandin-mediated effect of trifluoperazine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Direct determination of PGE2 synthesis by intact bladders showed no effect of 10 AM trifluoperazine under either basal or vasopressin-stimulated conditions. Furthermore, vasopressin failed to increase PGE2 synthesis, consistent with out previous report (19). Trifluoperazine's inhibitory effect persisted in the presence of the prostaglandin synthesis inhibitor naproxen, offering further evidence against a prostaglandin-mediated effect of trifluoperazine.…”
Section: Discussionsupporting
confidence: 90%
“…Immunoreactive prostaglandin E2 (PGE2) content was determined in duplicate by the immunoassay method of Dray et al (18) using specific antibody supplied by Boehringer Mannheim Biochemicals (Indianapolis, Ind). We have used this method previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…In other studies with mammalian nephron segments, lino and Imai (25) and Stokes and Kokko (26) found that exogenously applied PGE2 suppressed Na+ transport in isolated rabbit CCT. In both the CCT and in the toad urinary bladder, ADH has also stimulated the endogenous production of PGE2 (27,28). In these two tissues, inhibition of endogenous PGE production with prostaglandin synthetase inhibitors, such as indomethacin or meclofenamate, has increased the rate of sodium transport or the rate of osmotic water permeation (28)(29)(30)(31). For example, Holt and Lechene (31) demonstrated inhibition of ADH-stimulated Na+ transport in isolated rabbit CCT by prostaglandins produced within that tubule.…”
mentioning
confidence: 99%
“…In the toad urinary bladder and rabbit cortical collecting duct, prostaglandins El and E2 (PGE1) (PGE2)1 inhibit the change in water permeability induced by vasopressin but not by cyclic AMP (11)(12)(13)(14)(15), whereas inhibition of endogenous prostaglandin synthesis by cyclooxygenase inhibitors increases the response to vasopressin in both the toad bladder (18,(16)(17)(18) and mammalian kidney (19,20). Additionally, PGE2 biosynthesis has been demonstrated in the toad bladder (18,21,22), and basal rates of PGE2 production have been considered to influence the subsequent response to vasopressin (22).…”
mentioning
confidence: 99%